Validity of Biological Father As Marriage Guardian Against Syubhat's Son - Mushthafa, Mushthafa; AN, Rusydi; Nurliana, Nurliana (Jurnal Elsyakhshi, 2023)
This study aims to understand and find out how the marriage guardian is determined for children born as a result of a relationship Wath'i syubhat, be it a relationship Wath'i syubhat because of the contract and/or relationship Wath'i syubhat due to actions, as well as the legal consequences of having a biological father who is the child's marital guardian suspicious. Indeed, in Law No. 1 of 1974 concerning Marriage in article 43 paragraph (1) it is explained that: "illegal children only have a civil relationship with their mother and their mother's family". But in context Wath'i syubhat of course there are differences. In Wath'i syubhat, children born in this case can still have lineage with his biological father, and has the same rights as the rights of children born in a normal contractual relationship, such as a biological father being able to become guardian for his daughter from Wath'i syubhat. Child's marriage guardian watha' syubhat different from the marriage guardian of an adulterous child. Judging from the way it is mixed, if...watha’ syubhat there was a mix-up due to a misconception that the man and woman were a legal couple. While adultery sometimes there is an agreement or mutual consent, but they realize that the man and the woman have no one to legalize the intercourse. So the guardian marries the childwatha’ syubhat that's the person whogive away himself (biological father) if the child was born after six months afterdukhul (intercourse).